Utilizing Animaker in Producing Interactive Chemistry Learning Media on the Topic of Atomic Structure - Daril Ummahati; Jamil Suprihatiningrum (Postgraduate, University of Mataram, 2024)
Today’s learning process utilizes technological-based interactive learning media that improve students’ understanding of chemistry. Animaker is one of the AI-powered platforms to create animation and live-action videos. Therefore, this research tried to utilize Animaker to produce interactive learning media on atomic structure material, analyze the quality of the media based on material and media experts, as well as teachers, and determine students’ responses to the media. ADDIE model of research and development was used as the guideline in producing the media. First, needs analysis was carried out through literature reviews and preliminary studies. Second, the initial design was proposed, consisting of opening, main, and closing. Third, the design was then developed using Animaker website. In this stage, the media draft was validated by material and media experts. Two experts said that the media was excellent, although they provided feedback to improve the media. Some revisions were made before the media was delivered to teachers for quality testing. All teachers agreed that the media is of excellent quality (96.36%). The final media was then handed over to the student participants and they provided positive responses to the media. The Animaker is suitable for creating media that is interactive, interesting, and fun.